Dynamics of Political Campaign: A Study from 12th State Assembly Election in Manipur - Devi, Oinam Sarita (Indian Journal of Political Science)
In democracy, it is required to have well informed citizen. An uniformed citizen might bring constraint to a good government- developing a successful democracy. Political campaign is important for a citizen to have sufficient knowledge and information about the election process or formation of government. This paper highlight the different political campaigning strategies follow by parties/ candidate during 12th state assembly election in Manipur. It also shows the trends and nature that are followed during the campaigning process. It is determined that both the traditional as well as modern way of campaigning strategies were used during this election. Within this social media were used as the major platform to communicate with the voters. At the same time they also focus mainly on youths. The used of muscle power have increase significantly. The pre- election environments in the state were marked by unprecedented poll violence. - Reproduced
Keywords: Assembly election, democracy, Manipur, Political campaign